Europe and Europeanness in Early Modern Latin Literature : Fuitne Europa tunc unita? - Walser-Bürgler, Isabella, (Brill Research Perspectives in Humanities and Social Sciences., 2021)
The history of European integration goes back to the early modern centuries (c. 1400-1800), when Europeans tried to set themselves apart as a continental community with distinct political, religious, cultural, and social values in the face of hitherto unseen societal change and global awakening. The range of concepts and images ascribed to Europeanness in that respect is well documented in Neo-Latin literature, since Latin constituted the international lingua franca from the fifteenth to the eighteenth centuries. In Europe and Europeanness in Early Modern Latin Literature Isabella Walser-Bürgler examines the most prominent concepts of Europe and European identity as expressed in Neo-Latin sources. It is aimed at both an interested general audience and a professional readership from the fields of Latin studies, early modern history, and the history of ideas.